Processing conflicting information: facilitation, interference, and functional connectivity. - Cohen Kadosh, R; Cohen Kadosh, K; Henik, A; Linden, D (2008)
When a conflict task involves congruent, neutral, and incongruent conditions, it is possible to examine facilitation (neutral vs. congruent) and interference (incongruent vs. neutral) components. Very few studies investigated the brain areas that are specifically involved in facilitation or interference. We used functional magnetic resonance imaging while participants performed a magnitude conflict task (the size congruity paradigm). We observed four findings: (1) while most of the brain areas that were activated by conflict tasks showed interference effects, the intraparietal sulcus was the only region activated for both interference and facilitation components. (2) Two groups of participants could be distinguished based on the pattern of anterior cingulate cortex (ACC) activity, one with classical facilitation (congruent